IMPLEMENTATION ANALYSIS OF PHARMACEUTICAL MANAGEMENT INFORMATION SYSTEM IN THE DR. YAP EYE HOSPITAL YOGYAKARTA WITH HOT-FIT MODEL - Arum Pratiwi; Riswaka Sudjaswadi; Hari Kusnanto (Faculty of Pharmacy, Universitas Gadjah Mada)
Analysis on Pharmaceutical Management Information System (PMIS) application should be conducted for measuring or estimating the potential benefit purposes, observing potential problems that organization and its members might be faced, especially on pharmaceutical inventory management of a hospital. The results of the analysis may be used as the references in order to improve the existing potentials, so the PMIS will be able to carrying on the objective, vision and mission(s) of an organization. The HOT-Fit analysis model plays important role within information system namely Human, Organization, and Technology and harmonization among them in order to create Net Benefit from PMIS implementation. This research was conducted in Pharmaceutical Departement of Dr. Yap Eye Hospital Yogyakarta. This research was conducted within non-experimental quantitative- qualitative approach and applied case study framework. Questionnaires were analyzed by applying descriptive statistic methodology, Pearson correlation analysis, regression, multivariate statistic, and path analysis. Meanwhile, qualitative data were analyzed in order to establish the resume. The results of research showed that application of information system had not fulfilled the user expectation yet. On other side, harmonization among user-organization- technology really needs improvement to happen. There were strong correlations between Human-Technology and Organization-Technology. Human and Technology simultaneously affected the Net Benefit by 88,7%. Human and Organization simultaneously affected the Net Benefit by 87,8%. Organization- Technology simultaneously affected the Net Benefit by 75,3%. The most affective variable toward PMIS successful implementation were Human and Technology which means that certain improvement in the quality of technology & users ability would improve the probability to success of PMIS implementation in Dr. Yap Eye Hospital Yogyakarta.Keywords : Information system analysis, HOT-Fit, Dr. Yap Eye Hospital Yogyakarta